2014
DOI: 10.1080/13691058.2014.913812
|View full text |Cite
|
Sign up to set email alerts
|

‘Men usually say that HIV testing is for women’: gender dynamics and perceptions of HIV testing in Lesotho

Abstract: In Lesotho, men have lower HIV testing rates, less contact with HIV clinical settings, and less knowledge of HIV prevention than women. However, women’s HIV prevalence has consistently remained higher than men’s. This paper explores gender norms, sexual decision-making, and perceptions of HIV among a sample of Basotho men and women in order to understand how these factors influence HIV testing and prevention. Two hundred women and 30 men were interviewed in Lesotho between April–July 2011. Participants reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
97
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 30 publications
3
97
0
1
Order By: Relevance
“…This study’s findings are consistent with prior research demonstrating that while men’s enactment of masculinity often results in personal advantage, these same constructs and associated behaviors concurrently serve to configure vulnerabilities for men in terms of HIV acquisition, engagement and retention in HIV care, and HIV-related mortality (Baker et al, 2014; Braitstein et al, 2008; Cornell, McIntyre, & Myer, 2011; DiCarlo et al, 2014; Hawkins et al, 2011; May et al, 2010; Mburu et al, 2014; Ochieng-Ooko et al, 2010; Skovdal et al, 2011). We caution that findings of this study are not necessarily generalizable to all populations throughout sub-Saharan Africa and that participants’ accounts are potentially subject to recall and social desirability biases.…”
Section: Discussionsupporting
confidence: 88%
“…This study’s findings are consistent with prior research demonstrating that while men’s enactment of masculinity often results in personal advantage, these same constructs and associated behaviors concurrently serve to configure vulnerabilities for men in terms of HIV acquisition, engagement and retention in HIV care, and HIV-related mortality (Baker et al, 2014; Braitstein et al, 2008; Cornell, McIntyre, & Myer, 2011; DiCarlo et al, 2014; Hawkins et al, 2011; May et al, 2010; Mburu et al, 2014; Ochieng-Ooko et al, 2010; Skovdal et al, 2011). We caution that findings of this study are not necessarily generalizable to all populations throughout sub-Saharan Africa and that participants’ accounts are potentially subject to recall and social desirability biases.…”
Section: Discussionsupporting
confidence: 88%
“…Qualitative research by Siu, Wight, & Seeley (2014b) with men in Uganda showed that HIV testing was problematic for their masculinity because it potentially exposed their extra-marital partnerships, inhibited their opportunities for sex, and required them to admit that they potentially had a health problem and needed help. A study of HIV testing in Lesotho showed that being tested for HIV was perceived to conflict with men’s masculine self-presentation because it was perceived as feminised (DiCarlo et al 2014)…”
Section: Introductionmentioning
confidence: 99%
“…At the social level and related to social norms regarding HIV testing, there are concerns about the stigma associated with being seen at HTC clinics and that clinic staff will breach confidentiality (Angotti et al, 2009; Jürgensen, Tuba, Fylkesnes, & Blystad, 2012). Concerns about lack of confidentiality may be, in part, related to fear that that a main partner will suspect infidelity (DiCarlo et al, 2014; Mills, Beyrer, Birungi, & Dybul, 2012), and thus the interpersonal level is also important. In addition, at the structural level, inconvenience, time, and cost of travel to HTC clinics (Angotti et al, 2009; Gay, Croce-Galis, & Hardee, 2012; International Labour Organization, 2005), and the long waits (Gay et al, 2012; International Labour Organization, 2005) are barriers to health facility-based HTC for some (Stankard, LeTouzé, & Jones, 2014).…”
Section: Introductionmentioning
confidence: 99%